Port-au-Prince, Washington, Santo Domingo Premières leçons d'un embargo (Note) - Corten, André (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
After three pro-embargo resolutions from the OAS and five from the Security Council, an American military intervention authorized by the United Nations has enabled the democratically elected president Jean-Bertrand Aristide to return to office. This article seeks to trace the escalation from embargo to military intervention with reference to the transnationalization of social, economic, and political relations in which Haïti, the United States, and the Dominican Republic are directly involved. Large-scale population movements - deemed to be "threats to peace", and the importance of a "humanitarian" form of discourse and, even more so, a form of discourse about the "suffering" of the "unfortunate people of Haïti who are bearing... the full weight of sanctions" (Boutros-Ghali) are components of such transnationalized relations. These relations have developed in a setting that the boat people issue has determined in several ways, a setting where one can make out, on the one hand, a joining of forces between, among other people, the Haïtian priest-president and the U.S. congressional black caucus and, on the other hand, a shaky coalition comprising notably the president of the Dominican Republic, the Dominican archbishop, the Conference of Haitian bishops, the Vatican, and certain sectors of the American administration. Pena Gomez - a black man believed to be of Haïtian origin - ran as candidate for the Dominican presidential election and his candidacy was favoured for quite some time in the opinion polls. He ultimately failed, however, to provide an alternative in terms of political culture. The election on May 16, 1994 in the Dominican Republic was marked by incidents of fraud. The "international community", preoccupied as it was with re-establishing peace in Haiti, reacted feebly.